Comparison of marginal periosteal pedicle graft and bioactive glass with platelet-rich fibrin and bioactive glass in the treatment of intrabony defects - A clinicoradiographic study - M S Yasaswini; K V Prabhakara Rao; P Tanuja; Narendra Reddy Motakatla (Wolters Kluwer Medknow Publications, 2017)
Introduction and Objectives: The objective of the study was to compare clinically and radiographically the regenerative potential of marginal periosteal pedicle graft (MPPG) or platelet-rich fibrin (PRF) with a bioactive glass in the treatment of two- and three-wall intrabony defects. Methods: A total of 28 sites (bilateral or contralateral infrabony defects) from 14 patient were treated with MPPG (Experimental site A) and the other site was treated with PRF (Experimental site B). The clinical parameters, such as full-mouth plaque index (PI) and site PI, were recorded at baseline, 3, 6, and 9 months' postsurgery while sulcus bleeding index (SBI), probing pocket depth (PD), clinical attachment level (CAL), and gingival recession were recorded at baseline, 6, and 9 months. Radiographic evaluation was carried out to evaluate the defect fill, change in alveolar crest height, and percent defect fill at 6 and 9 months. Results: Results showed that both the experimental groups showed clinically and statistically significant reduction in mean PI, SBI, PD, radiographic defect depth, and gain in CAL. The percentage of defect fill at 6 months (70.55 ± 15.99 vs. 55.30 ± 11.87) and 9 months (84.55 ± 11.74 vs. 72.2 ± 9.91) was significantly greater in Site A compared to Site B. Conclusions: Within the limitations of this study, it can be concluded that both the treatment modalities showed the potential of enhancing bone regeneration. However, the use of marginal periosteal pedicle flap showed better improvement in clinical and radiographic parameters.